2005
DOI: 10.1007/s00330-005-2780-3
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral mamillary body atrophy after infarction of the posterior cerebral artery territory: MR imaging

Abstract: We describe herein magnetic resonance (MR) features of ipsilateral mamillary body atrophy after infarction of the posterior cerebral artery (PCA) territory. During the period May 2000 through July 2004, 13 patients with infarction of the PCA territory underwent cranial MR imaging in the chronic stage. Two 1.5-T scanners were used to obtain axial T1- and T2-weighted images with conventional spin-echo and fast spin-echo pulse sequences, respectively. The slice thickness was 6 mm, with a 2-mm interslice gap. Five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…In addition, secondary degeneration of the MB or Fx caused by PCA infarction could also be considered as differential diagnosis. Uchino et al reported five cases with ipsilateral MB atrophy after infarction of the PCA territory, all of which involved hippocampus (28). Careful evaluation of the vascular changes and existing cerebral infarction must be undertaken.…”
Section: Affected Ncmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, secondary degeneration of the MB or Fx caused by PCA infarction could also be considered as differential diagnosis. Uchino et al reported five cases with ipsilateral MB atrophy after infarction of the PCA territory, all of which involved hippocampus (28). Careful evaluation of the vascular changes and existing cerebral infarction must be undertaken.…”
Section: Affected Ncmentioning
confidence: 99%
“…Those small structures will sometimes be located in the interslice gap and the findings can easily be modified by the partial volume effect. Uchino et al reported that the tortuous and elongated basilar artery and crural segment of the PCA could compress the MB, resulting in asymmetry (28). Some other possible causes that influences those structures include compression by the edema following a large thalamic stroke, asymmetric positioning, and motion artifact or noise artifact.…”
Section: Affected Ncmentioning
confidence: 99%